A bolometer based on single-walled carbon nanotubes and hybrid materials. (December 2016) - Kopylova, D.S.; Boldyrev, N.Yu.; Iakovlev, V.Ya.; Gladush, Yu.G.; Nasibulin, A.G.
Abstract: We have designed a bolometric IR detector based on freestanding aerosol synthesised carbon nanotubes and hybrid graphene materials deposited on a film suspended over a hole in the substrate. In this case, graphene serves as an absorber. The effect of the amount of the deposited absorber on the spectral characteristics, voltage sensitivity, response time and noise of the bolometer is investigated. The best response time is observed for the samples of pristine carbon nanotubes, whereas the hybrid sample with the largest amount of graphene demonstrates the highest sensitivity to radiation. Moreover, we have measured and analysed the bolometer parameters as functions of the ambient pressure and temperature, which has allowed us to determine the optimum operating conditions for the device.